Record-High Electron Mobility Exceeding 16 cm2 V- 1 s- 1 in Bisisoindigo-Based Polymer Semiconductor with a Fully Locked Conjugated Backbone - Zhang, Weifeng (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.